Mindfulness in Palliative Care - the Healing Effect of the Present Moment - Miroslav, Světlák (Klinicka onkologie, 2020)
Palliative care is a multidisciplinary approach that improves the quality of life of patients and their families facing the problem associated with a life-threatening illness, through the prevention and relief of suffering. To help people relieve suffering effectively, the deep understanding of the nature of suffering and its dynamic is a crucial condition for it. The research of the mindfulness-based approaches in oncology and palliative care has repeatedly revealed that mindfulness meditation training is an efficient and feasible tool in helping people with the relief and modulation of suffering associated with cancer. In mindfulness training, we help people to develop an awareness that arises through paying attention, on purpose, in the present moment, non-judgmentally with the aim to convey them a deep inside to the fundamental principles of the mind functioning. This kind of inside brings them freedom in reaction to how they can respond to symptoms. The development of the skill to be in the present moment, with acceptance and non-judgmental manner to whatever arises in our experience represents the fundamental pillar in the background of well-being and mental health. From this point of view, the mindfulness-based programs and interventions should be an integral part of complex oncology and palliative care.
Keywords: paliativní péče; Psychotherapy; palliative care; nádory; quality of life; Mindfulness; Humans; všímavost; lidé; psychoterapie; mindfulness; Palliative Care; Neoplasms